Preservative‐free tafluprost in the treatment of open‐angle glaucoma or ocular hypertension in India: a phase III clinical trial. Issue 7 (13th June 2016) - Chabi, A.; Baranak, C.; Lupinacci, R.; Herring, W. J.
Summary: Aim: The aim of this study was to evaluate the efficacy and safety of preservative‐free (PF) tafluprost compared with PF timolol in Indian subjects with open‐angle glaucoma (OAG) or ocular hypertension. Methods: This was a randomised, multicentre, double‐masked, phase III trial. Subjects aged 18–80 years, following washout of current medication, with intraocular pressure (IOP) ≥ 24 and ≤ 36 mmHg in at least one eye were randomised in a 1:1 ratio to 0.0015% PF tafluprost or 0.5% PF timolol for 4 weeks. IOP was measured at 08:00, 10:00 and 16:00 hours at baseline and at weeks 2 and 4. The primary efficacy end‐point was the mean diurnal IOP change from baseline at week 4, and PF tafluprost was considered non‐inferior to PF timolol if the upper bound of the 95% confidence interval (CI) for between‐treatment differences was ≤ 1.5 mmHg. The secondary end‐point was the proportion of subjects with ≥ 25% reduction in IOP from baseline at week 4. Results: In total, 190 subjects were randomised, 95 each, to PF tafluprost and PF timolol treatment. PF tafluprost was non‐inferior to PF timolol with respect to diurnal IOP changes from baseline over 4 weeks. The mean PF tafluprost‐PF timolol difference in the diurnal IOP change was −1.7 (95% CI −2.6 to −0.7), suggestive of superiority for PF tafluprost. The secondary end‐point was achieved in a higher proportion of PF tafluprost group subjects. Both PF tafluprost and PF timolol were well‐tolerated with similar incidences of adverse events. Conclusions: PF tafluprost was safe and efficacious in reducing IOP in Indian subjects.